Epidemiology, surveillance and control of Rabies transmitted by Insectivorous Bats (Veterinary Science, 2021)
An exhaustive bibliographic search was carried out on epidemiology,surveillance and control strategies for Rabies variant 4 transmitted byinsectivorous bats. Likewise, as a case study, a retrospective study ofinsectivorous bats captured by passive surveillance and analyzed todetermine the presence of rabies virus was carried out in the Provinceof Río Negro, Argentina. The objective was to update the informationon the epidemiology of rabies variant 4 and to analyze the effectivenessof the control measures usually recommended by health services.The review carried out shows only 5 notifications in South Americacorresponding to canines and felines between 2009 and 2019 andwith regard to people, three cases were reported: in Chile in 1963 and2013 and in Colombia in 2012. The identification of insectivorous batscarrying rabies ranges from 4% to 15%. For its part, the veterinarypublic health service of the Health Ministry of Rio Negro collectedinsectivorous bats from passive surveillance activities. The bats weresent to the Laboratory of the Luis Pasteur Institute in the city of BuenosAires for identification of rabies virus. A total of 294 insectivorous batswere analyzed in 26 locations. The proportion of the infected ones was14.6% (95% CI 9.5-17.8) although there were no cases in dogs, cats orpeople. Insectivorous bats can be a risk factor for canines, felines, andhumans, although notifications of variant 4 cases in these species areextremely low in South America, so an evaluation of the recommendedand applied control strategy seems to be required, so far, as it is not cost-effective, and involves increasing operating costs in financial andhuman resources, proposing more efficient risk control alternatives.
Keywords: Rabies; insectivorous bats; surveillance; prevention